Glacial history and depositional environments in little Storfjorden and Hambergbukta of Arctic Svalbard since the younger dryas - Joe, Young Jin; Jang, Kwangchul; Forwick, Matthias; Laberg, Jan Sverre; Kong, Gee Soo; Kang, Moo-Hee; Yoon, Seok-Hoon; Nam, Seung-Il (Frontiers in Earth Science, 2022)
Geophysical and lithological data provide crucial information for the understanding of glacial history in Arctic Svalbard. In this study, we reconstructed the glacier-induced depositional environments of Little Storfjorden and its tributary, Hambergbukta, over the last 13 ka to better understand the glacial history of southeastern Svalbard. The combined uses of swath-bathymetry, high-resolution seismic stratigraphy, and multiple-proxy measurements of sediment cores allowed us to define five steps of glacier-induced depositional environments: 1) deposition of massive, semi-consolidated gravelly sandy mud (Facies 1) during re-advance or stand-still of the marine-based glaciers/ice streams in Little Storfjorden during Younger Dryas (13–12 ka); 2) deposition of massive mud to gravelly sandy mud (Facies 2A and B), during glacial retreat until the earliest Holocene (12–10.1 ka); 3) sediment winnowing by enhanced bottom currents during the early to middle Holocene (10.1–3.7 ka); 4) deposition of bioturbated sandy mud (Facies 3) with high productivity under seasonal sea ice conditions during the late Holocene (3.7–0.7 ka); and 5) deposition of (slightly) bioturbated sandy to gravelly mud (Facies 4) affected by glacier surges since Little Ice Age (LIA) (Facies 4). In addition to seismic stratigraphy, depositional patterns of IRD in Little Storfjorden indicate that the glacier surges in Hambergbukta occurred only after ~700 years BP. This suggests that the terminal moraine complex (TMC) represents the maximum extent of the LIA surges, which argues against the recent inference for the TMC formation during pre-LIA. This study shows the importance of multiple parameters to better understand the recent behavior of tidewater glaciers in the Svalbard fjords in response to rapid climate change.